Experiences of registered nurses supporting nursing students during clinical placement using a facility-based model: A mixed methods study. (February 2023) - Leon, Rebecca J.; Gilbert, Katriona; Ramjan, Lucie; Pizarro, Carlo; Salamonson, Yenna; Lombardo, Lien; Willis, Susan; Hunt, Leanne
Abstract: Background: An ageing workforce and increased vacancies has seen a steady growth in nursing student enrolments. This has created a need to re-think how to optimise existing clinical placement opportunities while ensuring quality student experiences and staff satisfaction in their support role. Objectives: To provide insights into the experiences and satisfaction levels of Registered Nurses who supported nursing students during clinical placement using a facility-based model. Design: A quasi-experimental design. Settings: Three wards in an acute care facility and Primary and Community Health within the Southwest of Sydney, New South Wales, Australia. Participants: Participants included Registered Nurses/Midwives, Facility-based liaison support staff, and Nurse Managers. Intervention: Within the 24/7 facility-based model, each nursing student was allocated to one Registered Nurse for the duration of the clinical placement period. The pair was rostered to complete the same day, evening, night, and weekend shifts. Methods: A cross-sectional survey related to staff satisfaction was administered to participants at two time points: (a) prior to the commencement of the intervention (baseline survey); and (b) at the completion of the intervention. Following the intervention participants were invited to a focus group or an individual interview. Results: There were no statistically significant changes in the levels of staff satisfaction from baseline to post-intervention; with personal fulfilment scoring the highest and workload the lowest. Staff who worked in the Primary and Community Health settings were less satisfied with this model of student support. Overall, most participants reported high personal satisfaction, professional growth and development opportunities yet acknowledged this came at a cost, with an increased workload. Conclusions: Participants were satisfied with the facility-based model in supporting student learning on clinical placement. The model is fit for purpose however it does need to be tailored to the contextual needs of nurses working in Primary and Community settings. Highlights: Optimising clinical placements requires reconsideration of current models of placement opportunities. Nurses were satisfied with the facility-based 24/7 model of facilitation. The facility-based model increased nurses' workload. The model of facilitation needs to be tailored to the contextual needs of Primary and Community.